Horseshoes, stylebooks, wheels, poles, and dummies: Objects of editing power in 20th-century newsrooms. (January 2015) - Keith, Susan
This essay examines five largely unsung artifacts of 20th-century newspaper journalism – the U-shaped copy desk, stylebooks, pica sticks, proportion wheels, and paper dummies – to tell a story about power shifts in US newsrooms. The essay also offers a new model of 20th-century newsroom eras, arguing that these objects of journalism mark what might be called the age of the copy desk, a time between the 1920s and 1970s when copy-desk editors exercised a quiet control over content. That power faded over the decades, symbolized by the disappearance of the distinctively shaped copy desk and the loss of relevance of most of the other tools. It was replaced, this essay argues, by eras of the writer from the 1970s into the 1980s and the designer from the late 1980s into the 21st century.